The Most Wanted - Jacquelyn Mitchard (New York Viking, 1998)
A correspondence between a 14-year-old Texas girl and a convict leads to love. A woman lawyer arranges a secret wedding and when the pregnant girl is banished from home, takes her in. The convict is a psychopath and tragedy follows when he escapes
Keywords: Literature (3GdCOHs; General -- Fiction; Mothers and daughters; Fugitives from justice -- Fiction; Prisoners' spouses -- Fiction; Female friendship -- Fiction; Women lawyers -- Fiction